Primary PCI in COVID-19 Pandemic: Be Cautious, It Might Reveal Itself Later - Arief Luthfi Parama; Dmitri Rifanda; Wishnu Aditya Widodo; Daniel Ruslim (Jurnal Kardiologi Indonesia, 2020)
Background: Acute ST-segment–elevation myocardial infarction (STEMI) is a disease of high mortality and morbidity, and primary percutaneous coronary intervention (PPCI) is the preferred therapy for patient in golden period or with hemodynamic instability.1,2 Currently the world has been declared under COVID-19 (coronavirus disease 2019) pandemic by the World Health Organization (WHO).3 Signs and symptoms of COVID-19 patients can mimic acute decompensated heart failure, or induce acute cardiovascular problem.3 Screening is key, but there are conditions where physicians might miss positive COVID-19 cases, especially in critical cardiovascular emergency. Case Illustration: A 60-year old male came to emergency room with breathlessness and chest pain 8 hours prior. He was diagnosed as acute inferior STEMI with acute lung edema and cardiogenic shock (KILLIP IV, acute heart failure wet and cold). COVID-19 screening was negative. Patient underwent PPCI, found to have total occlusion of right coronary artery (RCA) with thrombus and tight stenosis in left coronary artery (LAD). Successful PPCI to RCA was performed with TIMI 3 flow result, and hemodynamic improved. Ten hours after PPCI, hemodynamic deteriorated and peripheral oxygen saturation dropped. Patient was intubated and put on ventilator. Repeated chest X-Ray and thoracic CT showed lung condition has abruptly worsened – with ground glass opacity (GGO) found. His condition worsened quickly, and family agreed to a do not resuscitate (DNR) consent. Conclusion: Acute cardiovascular condition in COVID-19 Pandemics represent big challenges, especially in early diagnostic and cardiovascular intervention decision. We were presenting a case where signs and symptoms of COVID-19 might appear later. Therefore, in this pandemic era every emergency cardiovascular intervention with signs of respiratory problem should be performed as if patient was a positive COVID-19 case.